A block of sound absorbing material

By integrating β molecular sieves with precious metals into zeolite particles, the issue of aging in sound-absorbing materials is resolved, ensuring effective gas decomposition and sustained absorption performance in loudspeakers.

CN112261519BActive Publication Date: 2025-01-03SUZHOU QUAKER NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202011094033.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-04-16
Publication Date
2025-01-03
Estimated Expiration
2040-04-16

AI Technical Summary

Technical Problem

Existing sound-absorbing materials in loudspeakers, particularly zeolite particles with a silicon-to-aluminum ratio of at least 200, fail to completely prevent aging due to organic gases emitted by the speaker system, which leads to a deterioration in absorption performance.

Method used

Incorporating β molecular sieves containing precious metals, such as gold, silver, or platinum group metals, into the zeolite particles to catalytically decompose organic gases, thereby preventing aging.

Benefits of technology

The addition of precious metal-containing β molecular sieves effectively decomposes organic gases, maintaining the sound-absorbing performance of zeolite particles by preventing aging and ensuring consistent absorption efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112261519B_ABST
    Figure CN112261519B_ABST
Patent Text Reader

Abstract

The present invention provides a sound absorbing material block, which includes a zeolite material. The zeolite material includes zeolite particles containing precious metals. The precious metals in the zeolite material can catalytically decompose organic gases volatilized from a speaker device to prevent aging of the zeolite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of loudspeakers, and in particular to a sound-absorbing material block. Background Art

[0002] EP2003924A1 relates to a speaker system, a sound cavity including a speaker, the sound cavity is filled with a porous material, and the porous material is used as a gas absorbing material to physically absorb the gas in the sound cavity behind the speaker system. The porous material can be activated carbon, zeolite, silicon dioxide, aluminum oxide, zirconium oxide, magnesium oxide, black iron oxide, molecular sieve, fullerene carbon molecules and carbon nanotubes.

[0003] 201180040808.7 relates to a speaker system, which contains a speaker sound chamber and zeolite. The patent discloses that the zeolite material has zeolite particles with a silicon-aluminum ratio of at least 200, which solves the problem of aging of zeolite as an air absorbing material, especially aging caused by irreversible absorption of substances with higher vapor pressure.

[0004] In actual speaker system operation, zeolite particles with a silicon-to-aluminum ratio of at least 200 cannot completely solve the aging problem. In experiments, pure silicon zeolite with a silicon-to-aluminum ratio greater than 1000 also showed aging. It is mainly due to the organic volatile gases generated when the speaker system is working that cause irreversible aging of the absorber. Part of the organic gas is the organic volatile gas generated by the speaker unit when the speaker system is working, and part of the organic gas is the organic gas volatilized by the plastic sound cavity shell when the speaker system is working. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a sound absorbing material block.

[0006] In order to solve the above technical problems, the present invention provides a sound absorbing material block, wherein the sound absorbing material block comprises a zeolite material, and the zeolite material comprises zeolite particles containing precious metals.

[0007] Preferably, the zeolite material is intended for use in an area exposed to sound produced by a loudspeaker.

[0008] Preferably, at least a portion of the zeolite particles are β molecular sieves containing the noble metal.

[0009] Preferably, at least a portion of the zeolite particles is of MFI structure, and the mass of the β molecular sieve accounts for 1% to 10% of the total mass.

[0010] Preferably, the molar mass of the noble metal accounts for 0.1% to 5% of the beta molecular sieve.

[0011] Preferably, the precious metal is one or more of gold, silver and platinum group metals.

[0012] Preferably, the MFI structure zeolite is S-1 pure silica zeolite.

[0013] The sound absorbing material block of the present invention has the following beneficial effects:

[0014] 1. The precious metals in the zeolite material can catalyze and decompose the organic gases emitted by the speaker device, preventing the aging of the zeolite material;

[0015] 2. Beta molecular sieves containing precious metals are used to catalytically decompose organic gases. Beta molecular sieves have a large pore size of 0.7nm, and organic gases are easily adsorbed. The precious metal beta molecular sieves contain high catalytic activity and can decompose organic gases in an aerobic environment and convert them into carbon dioxide and water molecules.

[0016] 3. The pore size of MFI structured zeolite particles is well matched to the size of air molecules. In the prior art, they are usually used as sound-absorbing materials. However, due to the organic gas released by the speaker device, the MFI structured zeolite particles will be aged. Even using zeolite particles with a silicon-aluminum ratio of at least 200 cannot completely solve the aging problem. In the experiment, pure silicon zeolite with a silicon-aluminum ratio greater than 1000 also showed aging. In the present application, a zeolite material prepared by mixing MFI structured zeolite particles and β molecular sieves containing precious metals is used as a sound-absorbing material. Since the β molecular sieves containing precious metals decompose organic gases, the aging problem of MFI structured zeolite particles can be completely solved. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 It is a schematic diagram of the structure of the speaker device of the aluminum container.

[0018] Figure 2 It is a schematic diagram of an impedance curve test system of a loudspeaker device in an aluminum container.

[0019] Figure 3 It is a schematic diagram of a signal generator of a speaker device of an aluminum container.

[0020] Figure 4 It is a comparison chart of the impedance peak curve filled with gas absorbing material and the impedance curve without gas absorbing material.

[0021] Figure 5 This is a power-on aging test of a speaker device in an aluminum container, with a comparison chart of the gas absorbing material being unmodified zeolite and modified zeolite.

[0022] Figure 6 It is a schematic diagram of the structure of a loudspeaker device of a plastic container.

[0023] Figure 7This is an electrical aging test of a speaker device in a plastic container, with a comparison chart of the gas absorbing material being unmodified zeolite and modified zeolite.

[0024] Among them: 1. Speaker; 2. Aluminum container; 2'. Plastic container; 3. Zeolite material. DETAILED DESCRIPTION

[0025] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0026] The present invention provides a speaker device, comprising a speaker; a speaker container for accommodating the speaker; and a zeolite material exposed to a region where sound is generated by the speaker, wherein the zeolite material comprises zeolite particles containing a noble metal.

[0027] In a preferred embodiment, at least a portion of the zeolite particles is a beta molecular sieve containing the noble metal. At least a portion of the zeolite particles is an MFI structure, and the mass of the beta molecular sieve accounts for 1% to 10% of the total mass. The molar mass of the noble metal accounts for 0.1% to 5% of the beta molecular sieve. The noble metal is one or more of gold, silver and platinum group metals. The MFI structure zeolite can be S-1 pure silica zeolite. The speaker container is made of plastic.

[0028] The present application also provides a use of a zeolite material comprising zeolite particles containing a noble metal, wherein the zeolite material is exposed to an area where sound is generated by a speaker. The zeolite material comprises a β molecular sieve containing a noble metal and MFI structured zeolite particles.

[0029] In the present application, zeolite particles are porous minerals, usually aluminum silicate minerals, or pure silicon minerals.

[0030] The beta molecular sieve containing precious metals of the present application can be obtained by the following steps: adding a solution containing precious metal elements to a suspension of the beta molecular sieve, drying after thorough mixing, and calcining at a high temperature of 300 to 700°C to obtain the beta molecular sieve containing precious metals of the present application. The beta molecular sieve containing precious metals is mixed with MFI structure zeolite particles to obtain the zeolite material of the present application. The organic gases decomposed by the speaker device of the present application include: volatile compounds such as benzene, ketones, amines, alcohols, ethers, esters, acids and petroleum hydrocarbons, etc.

[0031] In a speaker system, the impedance curve is one of the important characteristics that reflect the speaker performance. The F0 corresponding to the impedance peak is generally considered to be the low-frequency resonance point F0 of the speaker system. In a speaker system with added gas absorption material, the lower the frequency corresponding to the impedance peak, the better the absorption effect of the absorber. After the absorber ages, the absorption effect deteriorates, and the frequency corresponding to the impedance peak will become higher, that is, F0 will become higher.

[0032] The inventor conducted the following comparative experiments during the development of the speaker device of the present application:

[0033] Experiment 1

[0034] like Figure 1 As shown, the speaker container is made of aluminum material, and the speaker 1 is placed in the speaker container 2 made of aluminum material. The speaker unit size is 12mm×17mm×3mm, the rear sound cavity volume is 0.5ml, and the zeolite material 3 is 100mg. The zeolite material is composed of MFI structure zeolite particles.

[0035] like Figure 2 As shown in the figure, it is the impedance curve test system of the loudspeaker device with aluminum sound cavity. Figure 4 The figure shows the comparison of the impedance peak curve filled with gas absorbing material and the impedance curve without gas absorbing material. Figure 4 It can be concluded that in the speaker system with added gas absorbing material, the frequency corresponding to the impedance peak is low.

[0036] Experiment 2

[0037] like Figure 3 The figure shows the power-on aging test of the speaker device with aluminum sound chamber. Experimental environment conditions: 27℃, 70% humidity; power-on voltage: 4.5V; input signal: 800HZ sine signal. Power-on time: 168Hrs. The electrical impedance curve and F0 are tested every 24 hours.

[0038] In this experiment, the unmodified zeolite is composed of MFI structure zeolite particles, the silicon-aluminum mass ratio of the MFI structure zeolite particles is 300, and the unmodified zeolite does not include a β molecular sieve containing a precious metal. The modified zeolite includes MFI structure zeolite particles and a β molecular sieve containing metal platinum, wherein the mass of the β molecular sieve containing metal platinum accounts for 10% of the total mass, and the molar mass of the precious metal accounts for 5% of the β molecular sieve.

[0039] The T-F0 curve of the speaker device with an aluminum speaker container is as follows Figure 5 The aging speed of unmodified zeolite is fast within 0-48 hours. After 48 hours, the aging speed decreases and tends to be stable.

[0040] The experiment shows that since the speaker will produce volatile gas when heated, and the aluminum container cannot produce volatile gas during use, within 0-48 hours, the unmodified zeolite absorbs the volatile gas and gradually ages. After 48 hours, the gas generated by the speaker itself evaporates and there is no volatile gas in the sound cavity, so the gas absorption material stops aging.

[0041] like Figure 5 As shown in the figure, within 0-24 hours, the concentration of volatile gas produced by the speaker itself is high, and the metal platinum in the modified zeolite has no time to decompose. After 24 hours, the concentration of volatile gas produced by the speaker decreases, and the metal platinum in the modified zeolite can be decomposed in time. Therefore, even a small amount of volatile gas will not cause the modified zeolite to age. After 48 hours, the gas produced by the speaker itself evaporates completely, and there will be no volatile gas in the sound cavity. In this experiment, the modified zeolite can stop aging after 24 hours. In this experiment, the F0 of the modified zeolite in the same period is smaller than that of the non-modified zeolite, indicating that the modified zeolite ages slower than the non-modified zeolite due to the presence of metal platinum.

[0042] Experiment 3

[0043] like Figure 6 As shown, the speaker device in this experiment uses a speaker container 2' made of plastic material. In actual use, the speaker container is usually also made of plastic. In this experiment, the speaker 1 is installed in the sound cavity of aluminum material, and the zeolite material 3 is filled in the rear sound cavity. The speaker unit size is: 12mm × 17mm × 3mm, the rear sound cavity volume is 0.5ml, and the gas absorption material is 100mg.

[0044] In this experiment, the unmodified zeolite is composed of MFI structure zeolite particles, the silicon-aluminum mass ratio of the MFI structure zeolite particles is 300, and the unmodified zeolite does not include a β molecular sieve containing a precious metal. The modified zeolite includes MFI structure zeolite particles and a β molecular sieve containing metal platinum, wherein the mass of the β molecular sieve containing metal platinum accounts for 10% of the total mass, and the molar mass of the precious metal accounts for 5% of the β molecular sieve.

[0045] like Figure 7 The figure shows the power-on aging of the speaker device with a plastic sound cavity. Figure 5 Compared with the power-on aging experiment of the speaker device with an aluminum sound cavity, it can be seen that the volatile organic gas generated by the plastic shell has a lasting effect on the aging of the non-modified zeolite.

[0046] Figure 7From the curve corresponding to the non-modified zeolite, it can be seen that within 0 to 48 hours, since both the speaker and the plastic container produce volatile gases, the non-modified zeolite ages quickly. After 48 hours, the speaker itself no longer produces volatile gases. Therefore, the aging speed of the non-modified zeolite slows down, but the plastic shell will continue to release volatile gases. The aging of the non-modified zeolite does not stop and will continue. This phenomenon was discovered by the inventor during long-term experiments. In the prior art, the influence of the volatile gases of plastic on the aging speed of sound-absorbing materials is usually ignored. Even the MFI structure zeolite particles with relatively high silicon-aluminum quality cannot stop aging.

[0047] exist Figure 7 In the experiment, the modified zeolite was added with β molecular sieve containing metal platinum. The platinum molecular sieve served as a catalyst to promote the decomposition of volatile gases. After 24 hours, the modified zeolite stopped aging. This experimental result shows that even if the plastic shell continuously emits volatile gases, the aging of the modified zeolite will not be affected because the platinum-containing Beta zeolite in the modified zeolite can promote the timely decomposition of volatile gases.

[0048] The zeolite material of the present application may be in granular form, and the granular zeolite material specifically includes a plurality of zeolite particles bonded together by a binder, and the particle size of the particles is 0.1 to 0.5. The mass of the binder accounts for 1% to 20% of the total mass of the zeolite material.

[0049] The zeolite material of the present application can also be made into a block structure, and a plurality of channels are provided in the longitudinal direction of the block structure, and sound-absorbing materials are filled between the channels. The center spacing between adjacent channels is 0.05mm-5mm. The zeolite particles are bonded together by an adhesive. The block structure also includes fibers, and the fibers are arranged in a criss-cross pattern, and the mass ratio of the fibers in the sound-absorbing material is not more than 50%. The zeolite material and the inner wall of the speaker container are supported by sound-absorbing cotton. The sound-absorbing cotton is made of melamine foam. The sound-absorbing cotton is interwoven with fiber filaments, and interconnected channels are formed between the interwoven fiber filaments. The binder is one of aluminum sol, silica sol, polyacrylate, polyurethane, epoxy resin, chloroprene rubber, silicone rubber, and polyvinyl acetate. The mass ratio of the binder in the sound-absorbing material ranges from 1% to 20%.

[0050] In the present application, the beta molecular sieve containing precious metals is used to catalytically decompose organic gases. The beta molecular sieve has a relatively large pore size of 0.7 nm, and organic gases are easily adsorbed. The beta molecular sieve containing precious metals has a high catalytic activity and can decompose organic gases in an aerobic environment and convert them into carbon dioxide and water molecules. The pore size of the zeolite particles with an MFI structure is well matched to the size of air molecules. In the prior art, they are usually used as sound-absorbing materials. However, due to the organic gases released by the speaker device, the zeolite particles with an MFI structure will be aged, and even the use of zeolite particles with a silicon-aluminum ratio of at least 200 cannot completely solve the aging problem. In the experiment, pure silicon zeolite with a silicon-aluminum ratio greater than 1000 also showed aging. In the present application, a zeolite material made by mixing zeolite particles with an MFI structure and a beta molecular sieve containing precious metals is used as a sound-absorbing material. Since the beta molecular sieve containing precious metals decomposes organic gases, the aging problem of zeolite particles with an MFI structure can be completely solved.

[0051] Any equivalent substitution or modification made by a person skilled in the art based on the present invention is within the protection scope of the present invention. The protection scope of the present invention shall be subject to the claims.

Claims

1. A sound-absorbing material block, characterized in that: The sound-absorbing material block comprises a zeolite material, wherein the zeolite material comprises zeolite particles containing a precious metal; the zeolite material is used to be exposed to an area where sound is generated by a speaker; at least a portion of the zeolite particles are β molecular sieves containing the precious metal; at least a portion of the zeolite particles are of MFI structure, the mass of the β molecular sieve accounts for 1% to 10% of the total mass; the molar mass of the precious metal accounts for 0.1% to 5% of the β molecular sieve; the precious metal is one or more of gold, silver and platinum group metals; and the MFI structure zeolite is S-1 pure silica zeolite.